Sonicate fluid inoculated into blood culture bottles does not improve diagnosis of periprosthetic joint infection caused by anaerobes. A retrospective analysis. (April 2020) - Rieber, Heime; Frontzek, Andre; Alefeld, Michael; Heinrich, Stephanie; Barden, Bertram; Jerosch, Jörg; Breil-Wirth, Andreas; Schmitt, Hubertus; Ulatowski, Martin; Götz, Sarah; Mullahi, Arjan; Fischer, Martin; et al.
Abstract: Background: In microbiological diagnosis of periprosthetic joint infection (PJI) there is much controversial discussion about culture media and incubation time, especially if anaerobic bacteria are the causative agents. This retrospective analysis was conducted to compare the results obtained by inoculation of sonicate fluid from prosthetic components into BD Bactec blood culture bottles with those obtained by our culture method using sensitive supplemented growth media. Methods: Twenty-eight cases were included in this study. For definition of PJI, the criteria of the Musculoskeletal Infection Society (MSIS) were considered. The quantity and time to positivity of anaerobes detected in sonicate fluid were monitored both from inoculated supplemented liver thioglycollate broth and anaerobic blood culture bottles. Furthermore, phenotypic testing was performed on the antimicrobial activity within the sonicate fluid. Results: The most frequently isolated microbes were Cutibacterium species, followed by Finegoldia magna, Parvimonas micra, Robinsoniella peoriensis, Clostridium species, Peptoniphilus harei and Slackia exigua . In 24 cases, the microorganisms became detectable within five days (median time 3.2 days) when sonicate fluid was incubated in supplemented liver thioglycollate broth, regardless of whether the patients had taken antimicrobial agents prior to surgery. However, when sonicate fluid was inoculated into anaerobic Bactec bottles, the median time to positivity was 7.4 days and only 12 cases (43%) were correctly identified. Sixteen cases remained negative after 14 days of incubation. Conclusion: Depending on the pathogen, incubation of sonicate fluid using blood culture bottles can support diagnosis of PJI but compared with our culture medium it is less efficient if anaerobes are the suspected cause of infection. Microbiological expertise is therefore indispensable to ensure reliable detection of these microorganisms in PJI until a gold standard for laboratory handling of anaerobes has been established. Highlights: Periprosthetic joint infection (PJI) is a serious complication in implant failure. In this study we investigated 28 cases of PJI associated with anaerobes. Sonicate fluid was analyzed by means of blood culture bottles (BCB). The results were compared to our culture-based method. We cannot fully recommend the BCB method, as anaerobes are not reliably recovered.